ANALISIS PENILAIAN TINGKAT KESEHATAN BANK (STUDY KASUS PADA PD. BPR BKK BOYOLALI KOTA) - Sundari Sundari (BHIRAWA, 2015)
The purpose of the research is to find out the bank health level of PD. BPR BKK Boyolali city base on CAMEL factor. The proposed hypothesis on the research is : Bank health level of PD. BPR BKK Boyolali city base on CAMEL factor is assumptions on ADEQUATE HEALTH CONDITION. Several steps are used in order to know how is bank health level can be measured, first, amassing report which is consist of Balance Sheet, Income Statement and others supporting report needed, second, analysing with ratio calculating of Capital Adequacy, Asset Quality, Management, Earnings Ability and Likuidity Sufficiency (CAMEL) also by analysing contravension level to Maximum Limit of Credit Allocation (BMPK), and at the last phase is whole of scores reached will be compared with standart score from Bank Indonesia. Based on the research, known that the healty level of PD. BPR BKK Boyolali city in HEALTH CONDITION with variated final scores between one year with another. It meant that hypothesis which acknowledge PD. BPR BKK Boyolali city at the year of research based on CAMEL factor in ADEQUATE HEALTH CONDITION is unacceptable. The implication expected from the research is giving a clearer view to the Management of PD. BPR BKK Boyolali Kota in policy making at the future in the form work plan and budgeting for the company to achieve a better result. In the work plan we can set up the right planning and strategy and also in the company’s budget planning we may do the efficiency which means that the realization of the expenses are enable to be implemented for supporting the strategy that should be applied. Management have to do evaluation and supervision for all work plan constantly to achieve company’s mission and goals have to find and survival on HEALTH condition. Keywords: the bank health level, CAMEL factor, strategic management